Evaluation of blood Pressure changes on exposure to sound frequencies in the youths of different ethnicity (Bangladesh Journal of Medical Science, 2022)
Objectives: To analyse the effect of exposure to different sounds of various frequencies on the blood pressure level of participants.Methods: Present study involved 160 medical students belonging to four ethnic races (Malay, Chinese, Malaysian Indians, Sri Lankans). Informed consent and the record of normal blood pressure was obtained before the study. Participants were exposed to three different sounds (Traffic sounds of high noise frequency; Waterfall sound of moderate noise frequency; Night sound in woods of low noise frequency) with specified intervals. The systolic (SBP) and diastolic blood pressure (DBP) of all the participants were recorded after each exposure. Data of SBP and DBP was analysed statistically by repeated measures ANOVA using SPSS.Results: Results showed statistically significant (p